Bacterial Chemotaxis to Naphthalene Desorbing from a Nonaqueous Liquid - Law, Aaron M. J. (American Society for Microbiology, 2003)
Bacterial chemotaxis has the potential to increase the rate of degradation of chemoattractants, but its influence on degradation of hydrophobic attractants initially dissolved in a non-aqueous-phase liquid (NAPL) has not been examined. We studied the effect of chemotaxis by Pseudomonas putida G7 on naphthalene mass transfer and degradation in a system in which the naphthalene was dissolved in a model NAPL. Chemotaxis by wild-type P. putida G7 increased the rates of naphthalene desorption and degradation relative to rates observed with nonchemotactic and nonmotile mutant strains. While biodegradation alone influenced the rate of substrate desorption by increasing the concentration gradient against which desorption occurred, chemotaxis created an even steeper gradient as the cells accumulated near the NAPL source. The extent to which chemotaxis affected naphthalene desorption and degradation depended on the initial bacterial and naphthalene concentrations, reflecting the influences of these variables on concentration gradients and on the relative rates of mass transfer and biodegradation. The results of this study suggest that chemotaxis can substantially increase the rates of mass transfer and degradation of NAPL-associated hydrophobic pollutants.